Self-Determination, Public Accountability, and Rituals of Reform in First Peoples Child Welfare - Libesman, Terri; Gray, Paul (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2023)
First Peoples continue to face intergenerational harms as a result of settler systems of intervention in the lives of their families, including the forced removal of children. First Peoples resistance includes advocacy for systemic change, in particular, focused on foundations of greater accountability in child welfare systems, and recognition of First Peoples’ right to self-determination. However, achieving these necessary structural changes remains a pressing challenge.Using the example of the recent Aboriginal-led review of child welfare in New South Wales (NSW), Australia, ‘Family is Culture’, this paper explores the cycle of inquiry and response, and the repeated failures to enable self-determination or strengthen public accountability and oversight. Drawing on concepts including legitimacy and the rule of law, we conceptualise this pattern of reviews as a ritual of redemption by settler child – welfare systems, distancing themselves from ‘past’ wrongs while refusing to address the harmful foundations of these systems, thereby perpetuating the violence imposed on First Peoples children, families and communities. This contrasts with First Peoples’ frameworks for child welfare reform, which must be urgently realised in order to establish such systems on more just and effective foundations.